2020
DOI: 10.1002/htj.21668
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally selective coating of nanoparticles (Co3O4:Cr2O3) incorporated in carbon to captivate solar energy

Abstract: Innovatory nanocomposite comprising nanomaterials Co 3 O 4 :Cr 2 O 3 and carbon (fuel ash) was designed to absorb solar energy. Different concentration ratios of Co 3 O 4 and Cr 2 O 3 nanoparticles were utilized as a dopant for fuel thin films synthesis via spin and casting methods on glass and aluminum substrates. The opticalproperties of the modified films demonstrated in the range of 250 to 1300 nm. The data were interpreted in terms of a phonon-assisted theory. Energy gap (E g ) of doped C was calculated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In [11], it was shown that nanoparticles-pigmented black paints can be engineered to simultaneously achieve solar-selectivity and durability at 750 ºC. Spectrally selective surfaces based on carbon surfaces doped with (Co 3 O 4 -Cr 2 O 3 ) nanocomposite for high-temperature operation have been investigated in [12], and in [13], thermally resilient hafnium carbide was used to realize a spectral selective cut-off absorber operating at high temperatures. A multilayer solar selective absorber consisting of Cu/Al 2 O 3 /Cr/SiO 2 /Cr/SiO 2 has a solar absorptance of about 0.954 and a thermal emittance of 0.196 at the temperature of 773 K [14].…”
Section: U Smentioning
confidence: 99%
“…In [11], it was shown that nanoparticles-pigmented black paints can be engineered to simultaneously achieve solar-selectivity and durability at 750 ºC. Spectrally selective surfaces based on carbon surfaces doped with (Co 3 O 4 -Cr 2 O 3 ) nanocomposite for high-temperature operation have been investigated in [12], and in [13], thermally resilient hafnium carbide was used to realize a spectral selective cut-off absorber operating at high temperatures. A multilayer solar selective absorber consisting of Cu/Al 2 O 3 /Cr/SiO 2 /Cr/SiO 2 has a solar absorptance of about 0.954 and a thermal emittance of 0.196 at the temperature of 773 K [14].…”
Section: U Smentioning
confidence: 99%
“…Various methods have been proposed to prepare solar selective absorbers (SSAs). One simple method is to coat a nanolayer on the substrate to achieve selective spectra, such as spin-coating, , dip-coating, , and spray-coating. , However, low adhesion between the coating and the substrate would limit its stability. Furthermore, physical vapor deposition , or laser sintering methods can be used to improve the high-temperature stability of SSAs.…”
Section: Introductionmentioning
confidence: 99%